2020
DOI: 10.4049/jimmunol.1900681
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Circulating Mucosal-Associated Invariant T Cells after Allogeneic Hematopoietic Cell Transplantation: Its Association with the Riboflavin Synthetic Pathway of Gut Microbiota in Cord Blood Transplant Recipients

Abstract: This information is current as RecipientsMicrobiota in Cord Blood Transplant Riboflavin Synthetic Pathway of Gut Transplantation: Its Association with the Allogeneic Hematopoietic Cell Mucosal-Associated Invariant T Cells after Reconstitution of Circulating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 52 publications
0
54
0
Order By: Relevance
“…Recently it was demonstrated that the ability of microflora to support thymic development of MAIT cells was dependent on riboflavin biosynthesis, and that providing exogenous 5-OP-RU was sufficient to reconstitute MAIT cell development ( 71 ). Recent studies also demonstrate the importance of gut microbiota and the presence of rib genes, on MAIT cell reconstitution after allogenic haematopoietic cell transplantation in humans ( 72 , 73 ). Dysbiosis in viral infections or changes to the gut microbiota have been shown to be associated with impaired MAIT cell responses ( 74 ) and it is hypothesized that dysbiosis in metabolic conditions also affects MAIT cells, altering their capacity to promote barrier integrity, and instead triggering a pathogenic, inflammatory MAIT cell response ( 75 ).…”
Section: Mr1-antigen Recognition In Physiological Settingsmentioning
confidence: 98%
“…Recently it was demonstrated that the ability of microflora to support thymic development of MAIT cells was dependent on riboflavin biosynthesis, and that providing exogenous 5-OP-RU was sufficient to reconstitute MAIT cell development ( 71 ). Recent studies also demonstrate the importance of gut microbiota and the presence of rib genes, on MAIT cell reconstitution after allogenic haematopoietic cell transplantation in humans ( 72 , 73 ). Dysbiosis in viral infections or changes to the gut microbiota have been shown to be associated with impaired MAIT cell responses ( 74 ) and it is hypothesized that dysbiosis in metabolic conditions also affects MAIT cells, altering their capacity to promote barrier integrity, and instead triggering a pathogenic, inflammatory MAIT cell response ( 75 ).…”
Section: Mr1-antigen Recognition In Physiological Settingsmentioning
confidence: 98%
“…They are innate-like T cells that highly express CD161 and a semi-invariant αβ TCRs that recognize microbial metabolites presented by MR1 [89]. MAIT cells can be activated in MR1-dependent and MR1-independent ways, although expansion requires circulating B cells and commensal microbiota [89][90][91][92]. In the allo-HCT setting, no associations between high MAIT cell numbers and protection from infections have been reported so far [93].…”
Section: Mait Cellsmentioning
confidence: 99%
“…In the allo-HCT setting, no associations between high MAIT cell numbers and protection from infections have been reported so far [93]. However, low frequencies of MAIT cells in the graft and post-HCT are associated with severe GvHD [74,[92][93][94][95], and higher numbers seem to be associated with improved overall survival [94].…”
Section: Mait Cellsmentioning
confidence: 99%
See 2 more Smart Citations